2014
DOI: 10.1111/bcp.12412
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics and haemodynamic effects of norepinephrine in hypotensive critically ill children

Abstract: AIMThe aim of the study was to investigate the pharmacokinetics and pharmacodynamics of norepinephrine in hypotensive critically ill children, including associated variability factors. METHODSThis was a prospective study in an 18-bed neonatal and paediatric intensive care unit. All children were aged less than 18 years, weighed more than 1500 g and required norepinephrine for systemic arterial hypotension. The pharmacokinetics and haemodynamic effects were described using the non-linear mixed effect modelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In a group of children including newborn infants NE has been shown to increase blood pressure on a dose dependent fashion [77]. One prospective cohort study has shown increased blood pressure with NE in newborns with congenital diaphragmatic hernia with no change in microcirculation measured by SDF imaging where peripheral microvascular bed is assessed [23].…”
Section: Evidence and Pd Effectsmentioning
confidence: 99%
“…In a group of children including newborn infants NE has been shown to increase blood pressure on a dose dependent fashion [77]. One prospective cohort study has shown increased blood pressure with NE in newborns with congenital diaphragmatic hernia with no change in microcirculation measured by SDF imaging where peripheral microvascular bed is assessed [23].…”
Section: Evidence and Pd Effectsmentioning
confidence: 99%
“…A pediatric norepinephrine pharmacokinetic and pharmacodynamics study (0.5–3 µg/kg/min) included 11 neonates and indicated that variabilities were related to weight, age, and severity of illness which was related to the production and clearance of norepinephrine ( 59 ). We found two retrospective studies of norepinephrine use in preterm neonates ( n = 48, <32 weeks and n = 30, <34 weeks) ( 60 , 61 ).…”
Section: Norepinephrinementioning
confidence: 99%
“…There is a significant variability in the PK and PD of exogenously administered epinephrine and norepinephrine. Several studies have investigated the PK/PD of epinephrine [203,204] and norepinephrine [205] in critically ill children. In critically ill children ranging from 0.5 to 16 years of age, epinephrine was reported to have a CL ranging between 15.6–79.2 mL/min/kg and the PK was characterized by a one-compartment model with linear elimination.…”
Section: Pharmacokinetic Studies In Critically Ill Childrenmentioning
confidence: 99%
“…The authors suggested that this may be due to changes in combination of different factors (e.g., plasma concentrations of platelets, electrolytes, calcium, caffeine) that alter the PK of catecholamines in critically ill children [204]. Similarly the CL of norepinephrine was 6.6 L/h/kg and the PK was well-characterized by a one-compartment model with linear elimination [205]. However, there was no difference in the PK of norepinephrine in critically ill children relative to adults [205].…”
Section: Pharmacokinetic Studies In Critically Ill Childrenmentioning
confidence: 99%
See 1 more Smart Citation